Fasting blood glucose as a predictor of progressive infarction in men with acute ischemic stroke. Issue 10 (October 2022) - Yu, Qiulong; Mao, Xiaocheng; Fu, Zhihui; Luo, Si; Huang, Qin; Chen, Qianxi; Li, Shumeng; Zhang, Jinchong; Qiu, Yuexin; Wu, Yuhang; Fang, Pu; Hong, Daojun; et al.
Objective: Blood glucose is related to early neurological deterioration in acute ischemic stroke, but multiple mechanisms are involved in early neurological deterioration, such as progressive infarction. This study aimed to determine whether fasting blood glucose (FBG) is an independent predictor of progressive infarction. Methods: From April 2017 to December 2020, we retrospectively enrolled 477 patients with acute ischemic stroke within 48 hours of onset. Demographic characteristics, clinical information, neuroimaging characteristics, and laboratory data were collected after admission. Results: We found that 147 (30.8%) patients had progressive infarction. Multiple regression analysis showed that high FBG concentrations (>7.66 mmol/L) were independently associated with progressive infarction. Sex subgroup analysis showed that high FBG concentrations were an independent predictor of progressive infarction in male patients (odds ratio, 2.559; 95% confidence interval, 1.279–5.121). In a receiver operating characteristic curve analysis, FBG concentrations were a predictor of progressive infarction in all cases, especially in male patients. The cutoff value of FBG in all patients and men was 7.155 mmol/L. Conclusions: FBG is an independent predictor of progressive infarction in patients with acute ischemic stroke within 48 hours of onset, especially in men. Patients with FBG concentrations ≥7.155 mmol/L are more likely to develop progressive infarction.